Lexical variation in Caribbean English: Allonymy from cognitive-onomasiological and ecolinguistic perspectives - Kozlova, T.; Bespala, L. V.; Беспала, Лілія Володимирівна; Klymenko, O. (My University, 2021)
The present paper seeks to further develop an interdisciplinary research into language variation and contact studies. Integrating cognitive-onomasiological and ecolinguistic approaches, it addresses lexical diversity in the Caribbean English. The permanent contacts between English and other local and transported languages have caused a wide range of modifications in the Caribbean English lexicon, including allonymy. Allonymy is treated as a contact-induced type of lexical variation leading to the formation of alternative names for the same referents. By tracing the sources of allonyms and disclosing cognitive mechanisms involved in their formation, this study explains the vitality of allonymic lexical items in the complex language ecology of the Caribbean region. It is argued that variation in naming processes is determined by speakers’ cognitive preferences as well as their cultural vigour that manifest in multilingual and multicultural ecology.
Keywords: Caribbean English; conceptual structure; language contact; language ecology; operational frame